A Cross‐Linked Interconnecting Layer Enabling Reliable and Reproducible Solution‐Processing of Organic Tandem Solar Cells. Issue 12 (9th February 2020) - Liu, Chao; Du, Xiaoyan; Gao, Shuai; Classen, Andrej; Osvet, Andres; He, Yakun; Mayrhofer, Karl; Li, Ning; Brabec, Christoph J.
Abstract: The performance of tandem organic solar cells (OSCs) is directly related to the functionality and reliability of the interconnecting layer (ICL). However, it is a challenge to develop a fully functional ICL for reliable and reproducible fabrication of solution‐processed tandem OSCs with minimized optical and electrical losses, in particular for being compatible with various state‐of‐the‐art photoactive materials. Although various ICLs have been developed to realize tandem OSCs with impressively high performance, their reliability, reproducibility, and generic applicability are rarely analyzed and reported so far, which restricts the progress and widespread adoption of tandem OSCs. In this work, a robust and fully functional ICL is developed by incorporating a hydrolyzed silane crosslinker, (3‐glycidyloxypropyl)trimethoxysilane (GOPS), into poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and its functionality for reliable and reproducible fabrication of tandem OSCs based on various photoactive materials is validated. The cross‐linked ICL can successfully protect the bottom active layer against penetration of high boiling point solvents during device fabrication, which widely broadens the solvent selection for processing photoactive materials with high quality and reliability, providing a great opportunity to continuously develop the tandem OSCs towards future large‐scale production and commercialization. Abstract : A robust and fully functional solution‐processed interconnecting layer (ICL) is engineered to chemically and mechanically protect the underlying photoactive layer against interface protonation and penetration of the high boiling point solvent without further thermal treatment. Organic tandem solar cells with various photoactive layers exhibit high reliability and good reproducibility, demonstrating the superiority of the crosslinked ICL.